Extension of AVHRR-based climate data records: exploring ways to simulate AVHRR radiances from Suomi NPP VIIRS data - K.-G. Karlsson; N. Håkansson; S. Eliasson; E. Wolters; R. Scheirer (Atmospheric Measurement Techniques)
The long series of multispectral measurements from the Advanced Very High Resolution Radiometer (AVHRR), which began in 1979, is now approaching its end, with the last remaining AVHRR sensor currently operating aboard EUMETSAT's Metop-C satellite. Several climate data records (CDRs) built on AVHRR data now face the end of their observational record. However, since many modern imagers contain AVHRR-heritage spectral channels, the potential for an extension of these AVHRR-based climate data records exists. This study investigates the possibility of simulating original National Oceanic and Atmospheric Administration-19 (NOAA-19) AVHRR channels from the Suomi National Polar-orbiting Platform (NPP) Visible Infrared Imaging Radiometer Suite (VIIRS) radiances using collocated AVHRR–VIIRS datasets from 2012–2013. Spectral band adjustments (SBAs) were derived using linear regression and neural networks (NNs). The NN approach produced the best results, and separating daytime from night-time conditions when simulating AVHRR channel 3B at 3.7 µm was key. Furthermore, daytime radiance corrections in this channel must depend on actual surface and cloud reflectances to be realistic, which was achieved only through the NN approach.